Cell-mediated immunity in weaned pigs - Frank Blecha; D S Pollmann; David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1982)
The stress of weaning lowers cellular immune reactivity in 2-, 3- and 4-week-old pigs. However, pigs weaned at 5 weeks of age do not exhibit altered cell-mediated immune reactivity. Those changes could alter disease susceptibility in young pigs.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Cell-mediated immunity; Weaned pigs